Analyzing the effect of Akoben programme on the environmental performance of mining in Ghana: A case study of a gold mining company - Bawua, S.A.; Owusu, R. (Journal of Sustainable Mining, 2018)
This study assessed the impact of Ghana's Environmental Protection Agency (EPA) Akoben programme, a rating and disclosure tool which seeks to promote better environmental performance in the mining and manufacturing industries in Ghana. Using a case study approach, the Akoben audit report card for a mining company was analyzed over a three-year period (2009–2011) based on 7-criteria – legal requirements, hazardous on-site waste management, toxic emissions management, environmental monitoring and reporting, best practice environmental management, complaint management, and corporate social responsibility. Key stakeholders' perceptions of the programme's suitability were solicited from the Ghana Chamber of Mines, EPA, and the mining company. Findings revealed that overall environmental performance over the three-year period under review was poor (2009 – 56.6%; 2010 – 65.6%; 2011 – 59.1%) with none of the years meeting the expected minimum limit, with the exception of legal requirements and corporate social responsibilities; the company failed in all other criteria. Specifically, both toxic and non-toxic waste emission discharges were major concerns as toxic parameters, such as for Arsenic, pH and Cyanide, were exceeded. Environmental monitoring and reporting was also a problem for the company. Stakeholders identified inadequate publicity, an absence of legal backing, and a lack of incentives for outstanding performances as the main weaknesses of the programme. Despite this, the stakeholders acknowledge the fact that the Akoben programme has improved the environmental performance of the mining companies because it puts their operations in check, although more can yet be achieved with regards environmental sustainability with this programme, if adequate measures including legal backing are put in place to ensure its continuity.
Keywords: Akoben; Environmental; Ghana; Mining; Performance; Rating